What we do when we #PrayFor communicating posthumanitarian solidarity through #PrayForMarawi - Crisostomo, Junesse d.R. (2021)
Access online through this link: https://www.plarideljournal.org/article/what-we-do-when-we-prayfor-communicating-posthumanitarian-solidarity-through-prayformarawi
Keywords: Tags (Metadata); Solidarity; Marawi City (Lanao del Sur); Social media and society